2015
DOI: 10.3832/ifor1116-008
|View full text |Cite
|
Sign up to set email alerts
|

Open field-applicable instrumental methods for structural and functional assessment of whole trees and stands

Abstract: © iForest -Biogeosciences and Forestry Introduction 1Proper management of forest ecosystems from a biological perspective is dependent on classification of the natural environment for the purposes of phytotechnology (e.g., thinning operations) and forestry management. Functional management goals may include timber production as well as other important functions of forests in the landscape, such as water sources for people, but also for control of climate, maintenance of biological diversity, recreation, etc. f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 114 publications
0
7
0
Order By: Relevance
“…, drought) as it was the case at our study site. Moreover, there is also evidence that when using 2 or 6 sample trees, the scaling error for estimates of Q s-mean is usually less than 12 and 7%, respectively (Cermak et al 2015).…”
Section: Methodsmentioning
confidence: 99%
“…, drought) as it was the case at our study site. Moreover, there is also evidence that when using 2 or 6 sample trees, the scaling error for estimates of Q s-mean is usually less than 12 and 7%, respectively (Cermak et al 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Social area is an aspect of stand area associated with a sample tree that accounts for its size and the size of neighboring trees as well as the available surrounding space [38,39]. Thus, each tree has its own growing area shaped by the trees surrounding it [52].…”
Section: Tree Social and Spatially-available Areamentioning
confidence: 99%
“…On the other hand, as a parameter that uses the dimension and distance between neighbors to express competition, AS is a good tool for explaining current tree radial increment. In addition, calculating AS for a sample tree, according toČermák et al [38,39], presumes that basal area at breast height is the best variable for tree size expression and for weighting distances between trees in a mutual tree competition evaluation. The weighted distances were solved by Krejza et al [42] and Pelz [57] and their results confirmed our finding that basal area is the best criterion to express tree dimension in competitive environment observations.…”
Section: The Orientation Of the Tree Social Area Extremesmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural attributes are crucial to determine information facilitating the management of forest ecosystems [2,3], to modify silvicultural practices [4,5], to quantify deforestation impacts on the carbon cycle and related impacts for global warming [6], and to assess productivity of forested areas in relation to forest composition [7] as well as in view of specific forest management practices [4,5]. Further, accurate estimates of structural variables are practical indicators for determining forest evolutionary history [8], monitoring forest sustainability [9], assessing insect infestation susceptibility [10,11], studying wildlife management and biodiversity [12], as well as forest water flux modeling [13]. Accordingly, there is an increasing need to generate accurate information regarding forest structural dynamics [14].…”
Section: Introductionmentioning
confidence: 99%